2009
DOI: 10.1128/ec.00256-08
|View full text |Cite
|
Sign up to set email alerts
|

The G-Alpha Protein GNA3 of Hypocrea jecorina (Anamorph Trichoderma reesei ) Regulates Cellulase Gene Expression in the Presence of Light

Abstract: Although the enzymes enabling Hypocrea jecorina (anamorph Trichoderma reesei) to degrade the insoluble substrate cellulose have been investigated in some detail, little is still known about the mechanism by which cellulose signals its presence to the fungus. In order to investigate the possible role of a G-protein/cyclic AMP signaling pathway, the gene encoding GNA3, which belongs to the adenylate cyclase-activating class III of G-alpha subunits, was cloned. gna3 is clustered in tandem with the mitogen-activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(157 citation statements)
references
References 79 publications
9
145
1
2
Order By: Relevance
“…Loss of the MAPK gene tmkA from T. virens (IMI304061) results in hyperconidiation in the light and dark (Mukherjee et al, 2003). However, the effect of this deletion is much less drastic than those observed in the Ga-protein mutants (Mukherjee et al, 2003(Mukherjee et al, , 2004Rocha-Ramirez et al, 2002;Schmoll et al, 2009;Zeilinger et al, 2005). In T. virens (Gv28.9), deletion of tvk1 results in a reduction in the production of conidia in solid medium and less intense conidial pigmentation compared with the wild-type (Mendoza-Mendoza et al, 2003).…”
Section: Heterotrimeric G Proteins and Map Kinase Cascadesmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of the MAPK gene tmkA from T. virens (IMI304061) results in hyperconidiation in the light and dark (Mukherjee et al, 2003). However, the effect of this deletion is much less drastic than those observed in the Ga-protein mutants (Mukherjee et al, 2003(Mukherjee et al, , 2004Rocha-Ramirez et al, 2002;Schmoll et al, 2009;Zeilinger et al, 2005). In T. virens (Gv28.9), deletion of tvk1 results in a reduction in the production of conidia in solid medium and less intense conidial pigmentation compared with the wild-type (Mendoza-Mendoza et al, 2003).…”
Section: Heterotrimeric G Proteins and Map Kinase Cascadesmentioning
confidence: 99%
“…In contrast, knockout mutations of tgaA (orthologue of tga1) and tgaB in T. virens do not differ from the wild-type in conidial phenotype (Mukherjee et al, 2004), and knockout mutants of gna1, a tga1 orthologue, in T. reesei are reduced or delayed in conidiation (Seibel et al, 2009). Recently, Schmoll et al (2009) demonstrated that the T. reesei Tga3 orthologue (GNA3) regulates cellulase expression in response to light and is itself induced by light exposure. It is not known whether GNA3 in T. reesei regulates conidiation by a mechanism similar to that of Tga3 in T. atroviride.…”
Section: Heterotrimeric G Proteins and Map Kinase Cascadesmentioning
confidence: 99%
“…Tga3 was further found to be essential for the transmission of signals that regulate recognition of the prey fungus and attachment to its hyphae (614). In T. reesei, both GNA1 (TR_123302) and GNA3 are involved in the regulation of cellulase gene transcription by light (617,618). However, the fact that constitutive activation of GNA3 resulted in a 10-fold upregulation of cellulase gene expression in light but did not lead to inducer-independent cellulase formation rules out that GNA3 transmits the crucial signal for the presence of cellulose (618).…”
Section: The Heterotrimeric G-protein Pathwaymentioning
confidence: 99%
“…Nutrient deprivation or different nutrient sources are universal signals for conidiation, and light is a determinant for the utilization and/or uptake of specific carbon sources by Trichoderma species (132). Several components of the heterotrimeric G-protein and cAMP pathways and two Ras GTPases impact sporulation, often in a light-and nutrient-dependent manner (103,109,112,115,131,147). Conidiation by T. viride and T. atroviride is strongly carbonsource dependent in light and darkness (21,39).…”
Section: T Reesei Genome Publishedmentioning
confidence: 99%